Too Gay for the Evangelicals, Too Evangelical for the Gays: A Narrative and Autoethnographic Study of a Celibate–Gay Testimony - Luke Aylen (Religions)
The ecclesiastical discourse in Britian over homosexuality has included a significant focus on the narratives and experience of LGBTQ+ people. However, the relationship between and respective authority given to human experience and the Bible within church debates remains a matter of contention, especially among evangelicals committed to ‘biblicism’. This study considers how even those unconvinced about experience as a ‘source’ of theology might still engage with queer narratives as an invitation for personal and cultural reflexivity and how the plausibility of theological claims might be tested whilst still prioritising Scripture. I examine testimony through a three-stage study. First, I conduct a narrative analysis of audiovisual recordings of my own prior practice of testimony as a celibate gay evangelical. Second, I offer up new, autoethnographic, thick descriptions of three pivotal crisis moments. Third, I theologically reflect upon these in relation to Romans 12.1–2 and the meta-theme of identity formation. I argue that LGBTQ+ testimonies have the potential to illuminate and thus transform heteronormative cultural patterns within the church; I argue that Christian identity formation must include the central integration of God’s identification of a person in Christ; and I attempt to model how Christians might cautiously discern God’s activity within a practice of testimony.